Problem-based learning: student perceptions of its value in developing professional skills for engineering practice. (2nd November 2019) - Beagon, Úna; Niall, Dervilla; Ní Fhloinn, Eabhnat
ABSTRACT: This study explores students' perceptions of the effectiveness of a Problem-Based Learning (PBL) design project, taken as part of a first-year engineering module, in developing professional skills needed for engineering practice. Students completed surveys before and after the PBL group project, and produced personal reflections on the process. The closed survey questions were analysed quantitatively and the main themes from the reflections outlined using General Inductive Analysis. Students rated themselves as having improved across a range of professional skills as a result of the project, with particular emphasis on teamwork, communication skills, understanding of the design process and self-directed learning. In addition, they highlighted improved confidence, as well as new friendships they developed, an important element of a module like this as they transition from secondary to higher education. They were particularly positive about the scaffolded approach taken within the PBL project in terms of its contribution to their learning.